PENGEMBANGAN SEBUAH METODE INTERAKTIF UNTUK PENYELESAIAN MASALAH PROGRAM LINIER BILANGAN BULAT KELAS STOKASTIK MULTIOBJEKTIF - Suparni Suparni (IAIN PADANGSIDIMPUAN, 2016)
Decision problems of stochastic or probabilistic optimization arise when certain coefficient of an optimization model are not fixed or known but are instead, to some extent, stochastic (or random or probabilistic) quantities. This paper focused on multi objective stochastic optimization. We propose a method for solving a multi objective chance constraints integer programming problem based on interactive approach. We assume that there is randomness in the right-hand sides of the constraints only and that the random variables are normally distributed.